Sharing milk : intimacy, materiality and bio-communities of practice - Carter, Shannon; Reyes-Foster, Beatriz M. (Gender and sociology, 2020)
Using a bio-communities of practice framework, this thought-provoking empirical analysis explores the emotional and material dimensions of the growing phenomenon of milk sharing in the Global North and its implications for contemporary understandings of infant feeding in the US, providing new insights into a much-debated topic.